...at G + gL = 8pi T. [See source] In which case, the

**LHS**is the geometric curvature of space time (the origin of gravity effects) and...2 Answers · Science & Mathematics · 04/12/2012

...;=> ∫ 1/(g+k·v²) dv = - ∫ dt Integration on

**LHS**leads to the inverse tangent: ∫1/(1+z²) dz = arctan(z) => ∫ 1/(1...1 Answers · Science & Mathematics · 14/04/2008

...triangle, with dimensions L^2! In YOUR question, the

**LHS**(r) is a RADIUS, and thus has the dimension of a (single) length...4 Answers · Science & Mathematics · 28/08/2007

...by gravity equals change in kinetic energy. (1/2)mv^2 + mgh=(1/2)mv^2 the

**LHS**is the initial velocity and the RHS is the final velocity, notice that...2 Answers · Science & Mathematics · 17/12/2008

...(x) = tan²x Dealing with the first term on the

**LHS**: csc(x) = 1/sin(x), so**LHS**1 = sin(x)/(csc(x) - 1) * sin(x)/sin(x) = ...1 Answers · Science & Mathematics · 07/12/2016

...the blocks as point masses. I_point mass = m*r^2 I_

**LHS**= m*l1^2 I_RHS = m*l2^2 I_total = I_RHS + ...2 Answers · Science & Mathematics · 31/10/2014

...letter) O (assume) Given Ax = -6.4 let OA’ = 6.4 towards

**LHS**of the point O (towards (-) side of x-axis) Ay = 7.8 let ...2 Answers · Science & Mathematics · 14/11/2012

...variable 'i' and the derivative. To solve for i(t), we need to re-write the

**LHS**into a derivative form (di/dt) and integrate. We need to define an integrating...2 Answers · Science & Mathematics · 26/12/2006

...v + 79.59 ]*[ v – 79.59 ] } = - (0.081566)*dt Rewriting the left hand side (

**LHS**) of (4) as a sum of partial fractions of the form .......... A/ [ v...2 Answers · Science & Mathematics · 28/04/2010

...for x and y. Because I added some extra terms on the

**LHS**, I must add the same amount to the RHS. (x+4)^2 + (y+1)^2 = -18 + (8...1 Answers · Science & Mathematics · 09/06/2011